MEASUREMENT OF RESIDUAL STRESSES BY THE NEUTRON DIFFRACTION TECHNIQUE IN A WELDED JOINT - ZAOUI, M; SLAMANI, M (Courrier du Savoir, 2016)
The welds are the site of high residual stresses, localized in the vicinity of the weld cracks. Their presence caused many type of damage modes as stress corrosion, fatigue, sudden failure and increasing the temperature of ductile-brittle transition. Residual stresses in restrained welds and weld repairs are very complex. The heat treatment affects the value and distribution of residual stresses in the specimen. This peak stress in all three samples occurred not at the toe, but in the middle of the weld bead, where the yield stress is higher. The transverse residual stresses of around half the maximum value of longitudinal stress have been observed. The use of the neutron diffraction (ND) technique for residual stress measurements is described. In addition, studies of macrostructure and hardness were conducted. The results of different tests conclude the influence of heat treatment on residual stresses in welds.